Proceedings of the 24th International Symposium on Advancement of Construction Management and Real Estate - Ye, Gui; Yuan, Hongping; Zuo, Jian (Springer Nature Singapore : Imprint: Springer, 2021)
XIX, 2252 p. 568 illus., 365 illus. in color.